Organic farming: assessment of the perception of practicing tribal farmers in Jharkhand - PANDEY, BRIJESH; SINGH, AJEET KUMAR; SINGH, NIDHI; RAJAN, NEHA; KUMAR, ANJANI; SINGH, RAVINDRA KUMAR; KESHAVA (The Indian Journal of Agricultural Sciences, 2022)
Organic farming aims to produce healthy and non-toxic food for consumers using natural inputs to eliminate any substance from farming system which is harmful to human as well as soil health. Organic farming is not a new concept but a traditional farming system with modern scientific techniques. Realizing the long-term positive impact of organic farming, Government of India is also promoting the organic farming on a large scale. In line with this, three villages of Angara block of Ranchi District have been developed as fully organic villages. To assess the general, attitudinal and control belief among tribal farmers towards organic farming, a study was conducted in two Participatory Guarantee System (PGS) certified villages namely Dhurleta and Budhakocha of Ranchi district in Jharkhand state during the year 2019–20. Data for the study was collected through personal interview of the tribal farmers practicing organic farming using structured interview schedule developed for the purpose. A total of 50 farmers (25 farmers from each village) selected through systematic random sampling method formed the sample of the study. Findings of the study showed that about 76.80% farmers believed that organic farming is good while 61% of the respondents had favourable attitudinal belief towards organic farming. Majority of the population agreed that disease, pest control, marketing and complexity in certification are the major setbacks in large scale adoption of organic farming.